Analysis of Cross-Border Capital Flow Management and Financial Stability in the Era of Globalization - Su Hongrui (SHS Web of Conferences)
Globalization has accelerated cross-border capital flows, and the unrestricted movement of capital worldwide has stimulated the global economy’s growth. However, this free flow of capital can also heighten the volatility of financial markets and the susceptibility of economies, posing a potential risk to financial stability. This study uses quantitative and qualitative analysis to examine the impact of cross-border capital flow on financial stability in the era of globalization, as well as the strategies and mechanisms for managing these capital flows. Through case studies, we analyze the role of national regulation and international coordination in maintaining financial stability and the existing challenges. The research discovered that intentional control of capital flow can decrease the extreme instability of financial markets, combined with open and coordinated global regulatory mechanisms, which will successfully avoid and mitigate financial crises. In conclusion, this paper suggests that the key to ensuring financial stability and promoting sustainable development lies in exploring cooperation at global and regional levels and establishing a multilateral regulatory framework.